Environmental distribution, transport and ecotoxicity of microplastics: A review. Issue 1 (15th July 2020) - Du, Jia; Zhou, Qingwei; Li, Huanxuan; Xu, Shaodan; Wang, Chunhui; Fu, Li; Tang, Junhong
Abstract: Microplastics (MPs) have become a global environmental pollutant because of their unique properties. The extensive MP toxicity reports have focused on the aquatic environment, while the pervasive MP contamination in the soil and air has largely been overlooked. This review summarizes the abundance, sources and transport of MPs in different environments. It analyzes the toxicity of MPs based on various environmentally relevant bacterial, cellular, plant, aquatic animal and mammalian test groups, using both in vitro and in vivo experiments. The combined toxicity effects of MPs and various other environmental pollutants on ecosystems are also discussed. Currently, data on the adverse effects on combined MP toxicity are very limited. Thus, a systematic assessment of the environmental risk in different environments and in various species from MPs is challenging. Thus, this review proposes the possible risks and identifies the knowledge gaps posed by MPs to food safety and human health. Abstract : This review summarizes the environmental occurrences and transport of MPs in different environments. It also analyzes the potential threat to aquatic animals, terrestrial animals and plants using both in vitro and in vivo toxicity studies. The combined toxicity evaluation of MPs and various other environmental pollutants on ecosystems are also discussed. Ultimately, some knowledge gaps and research directions are proposed herein.